PENGARUH WARNA CAHAYA LED MERAH, BIRU, KUNING DAN MEDIA TANAM TERHADAP PERTUMBUHAN DAN PRODUKSI MICROGREEN BAYAM MERAH (Amaranthus gangeticus) - santi nur aini; Siti Asmaniyah Mardiyani; Indiyah Muwarni (AGRONISMA, 2021)
Red spinach is quite easy to cultivate so it can be planted and harvested at microgreen age. Microgreens are vegetables that are harvested 7-21 days after germination. Microgreens are functional foods because they have many health benefits. This study aims to determine the interaction between red, blue, yellow LED light colors and growing media on the growth and production of red spinach (Amaranthus gangeticus) microgreen. This research is a box experiment using a Divided Plot Experiment Design. The results showed that there was an interaction between the color of the LED and the growing media on the growth of microgreen red spinach. The combination of C1M3 (Red LED + Sand & Compost) with an average of 4.24 cm and C2M3 (Blue LED + Sand & Compost) with an average of 4.44 cm resulted in higher plant heights at 7 DAP. Different types of planting media on microgreen red spinach had a significant effect on growth where compost sand media produced the highest plant height, which was 4.55 cm at 14 DAP. Separately, the average yield tends to be higher in the red and blue LED treatments, as well as the combination of sand and compost media. Compost sand combination (M3) gives the best results supported by fresh weight parameters with an average of 9.35 g. In the C0M1 quality parameter, it shows that treatment tends to be better supported by the TPT parameter with an average value of 2.50. Based on the results of this study, it can be recommended that the cultivation of red spinach microgreens in planting boxes can be done using red and blue LEDs and a combination of compost sand planting media to pay attention to micro elements that affect microgreens for better growth.